Uso de la red social Instagram y su impacto en la audiencia de Diario La Prensa” Periodo enero – junio 2023 - Mejia Chasipanta, Darwin Eddy (2025)
The objective of the research work was to analyze the impact of the Instagram account of "Diario La Prensa" on its audience. The research considered the strategies used by the media for using its Instagram account. It was essential to apply matrices to know the strategy, their use, and if the media uses them correctly. On the other hand, the researcher conducted surveys of the followers of "Diario La Prensa," where it was vital to determine the population sample due to the large number of followers the profile has. The survey comprises 13 questions, which are helpful for the research to determine the type of journalistic genre preferred, how the audience interacts with the publications, if the profile is relevant, and their preference regarding local or national news. Different communicative processes, such as Shannon and Weaver's theory, support all the above mentioned since it explains how everything has a process that has to follow the dissemination of news. It was necessary to adapt it to the present using social networks similar to traditional media. On the other hand, the researcher applied interviews with the media expert and two external experts, which gave weight to the investigation and the theories. The results of the interviews showed that the media's strategies and how the audience interacts with the publications were positive. At the end of the research, it was essential to set a manual strategy for news media in the social network Instagram, considering the experts' recommendations and the audience's responses in the survey conducted.